On the Issue of the Organizational Nature of the Grid Connection Agreement - M. T. Khamidullin (Informaciâ i Innovacii)
Subject/topic. Technological connection agreement in the context of the theory of organizational relations in Russian civil law. Goals/objectives. In the article, the author examines the doctrinal provisions and materials of judicial practice on the legal nature of the technological connection agreement. It is compared with the organizational contract. The author highlights common features that make it possible to attribute the technological connection agreement to organizational agreements and features that distinguish these two agreements. Separately, the nature of interaction between the parties to the technological connection agreement, due to the organizational nature of their relations, is considered. Methodology. The methodological basis of the research consists of General methods of cognition; General scientific methods of research, including the system and logical method, as well as analysis, synthesis, analogy, formal legal, etc. Conclusion and Relevance. Based on the analysis, the author makes conclusions about the qualification of the technological connection agreement as a property and organizational agreement that organically combines elements of organizational and property agreements. For the first time in the legal literature, the author formulated his own definition of the category of property-organizational contract that he deduced.